Forensic toxicology : medico-legal case studies - Rao, Kalipatnapu N. (Boca Raton, Florida : CRC Press, 2012)
'This book illustrates how analytical methods are set up, results are generated, and quality control is maintained in clinical toxicology laboratories. Geared to the practicing toxicologist who must be able to give a deposition and write a report for legal use, the book describes fifty case studies to show the progression of toxicology findings from the laboratory to the courtroom. Both civil and criminal cases are addressed, and interesting issues are explored, such as whether consumption of poppy seeds can result in a positive lab test for opiates'--
Includes bibliographical references and index.
Keywords: Forensic toxicology -- Case studies; Criminal investigation; Forensic toxicology; United States; Case Reports